Malaysia’s political economy : - Gomez, Edmund Terence (Cambridge University Press, 1999)
This book is an insightful and accessible analysis of contemporary Malaysian business and politics. Using the concepts of rent and rent-seeking as tools to study the Malaysian political economy, the authors explore how political patronage influences the accumulation and concentration of wealth. The book considers the impact of party politics and economic development on the relationship between politics and business in Malaysia, and provides up-to-date discussions of government-led change in Malaysia's business community, including the emergence of a Malay business class. In this revised edition, the authors examine how the 1997 Asian currency, liquidity and financial crises have impacted on Malaysia's economy. Their discussion canvasses various economic policy responses, including capital control measures, as well the ensuing economic recession and political turmoil.